Citizen Science and Community Engagement in Tick Surveillance—A Canadian Case Study - Julie Lewis (Healthcare, 2018)
Lyme disease is the most common tick-borne disease in North America and Europe, and on-going surveillance is required to monitor the spread of the tick vectors as their populations expand under the influence of climate change. Active surveillance involves teams of researchers collecting ticks from field locations with the potential to be sites of establishing tick populations. This process is labor- and time-intensive, limiting the number of sites monitored and the frequency of monitoring. Citizen science initiatives are ideally suited to address this logistical problem and generate high-density and complex data from sites of community importance. In 2014, the same region was monitored by academic researchers, public health workers, and citizen scientists, allowing a comparison of the strengths and weaknesses of each type of surveillance effort. Four community members persisted with tick collections over several years, collectively recovering several hundred ticks. Although deviations from standard surveillance protocols and the choice of tick surveillance sites makes the incorporation of community-generated data into conventional surveillance analyses more complex, this citizen science data remains useful in providing high-density longitudinal tick surveillance of a small area in which detailed ecological observations can be made. Most importantly, partnership between community members and researchers has proven a powerful tool in educating communities about of the risk of tick-vectored diseases and in encouraging tick bite prevention.